Exploring Game-Based Language Learning Applications: A Comparative Review of Quizwhizzer, Oodlu, Quizalize, and Bamboozle - Afif Ikhwanul Muslimin; Francisca Maria Ivone (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
The rapid growth of technology has affected sectors of human life, including English Language teaching (ELT). Hence, English language teachers (ELLs) should garb the benefits of technology to elevate their teaching outcomes i.e., creating a more engaging classroom. Nevertheless, selecting the most suitable applications to support teaching is not easy. Hence, this research aims to review four Game-Based Language Learning (GBLL) Applications: Quizwhizzer, Oodlu, Quizalize, and Bamboozle to assist ELLs to make decisions. This study employed a comparative review method based on Chapelle's (2001) technology evaluation criteria. These criteria include language learning potential, meaning focus, learner fit, authenticity, impact, and practicality. Through the application of these criteria, the article explores and assesses the features, pedagogical approaches, user experiences, and language learning outcomes facilitated by each application. The findings showed that all applications had the potential to support English language teaching. Then, the majority exhibited positive impacts based on scientific research findings and reflected positive analysis from the lens of Chapelle’s (2001) evaluation criteria. However, drawbacks appeared due to each application’s special feature i.e., the limited uploadable file formats and getting full access to application features. Hence, this study suggests further investigations due to its limitation.